VideoFlip: Adversarial Bit Flips for Reducing Video Service Quality - Chang, Jung-Woo; Javaheripi, Mojan; Koushanfar, Farinaz (2023 60th ACM/IEEE Design Automation Conference (DAC), 2023)
Video compression is a critical component in streaming applications that maximizes users' quality of experience (QoE) while satisfying the underlying bandwidth constraints. In this paper, we demonstrate the first hardware-based fault-injection attack on video compression, dubbed VideoFlip. The attack identifies and alters a few bits inside the video compression model to achieve one or more of the following adversarial goals: (1) increasing the bitrate and (2) degrading the quality of the compressed video. Extensive evaluations show VideoFlip irresistibly downgrades video compression performance for various models and video datasets while being resilient to contemporary defenses against hardware-based bit flips.